2021
DOI: 10.1186/s13047-021-00477-5
|View full text |Cite
|
Sign up to set email alerts
|

Duration of total contact casting for resolution of acute Charcot foot: a retrospective cohort study

Abstract: Background Charcot neuroarthropathy (Charcot foot) is a highly destructive joint disease of the foot and ankle. If there is delayed diagnosis and treatment, it can lead to gross deformity, instability, recurrent ulceration and/or amputation. Total contact casting (TCC) is a treatment commonly used to immobilise the foot and ankle to prevent trauma, further destruction and preserve the foot structure during the inflammatory phase. At present, there is limited Australian data regarding the durati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
57
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(59 citation statements)
references
References 68 publications
(170 reference statements)
0
57
0
2
Order By: Relevance
“…Body mass index (BMI) was reported only in three studies 21,26,37 and only one study reported ethnicity 38 (Table ). CN location was reported using either the Sanders–Frykberg classification ( n = 10), 23–30,32,39 and Brodsky classification ( n = 1), 34 in detail, 22 available only for those in remission 38 or unreported ( n = 6) 21,31,33,35–37 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Body mass index (BMI) was reported only in three studies 21,26,37 and only one study reported ethnicity 38 (Table ). CN location was reported using either the Sanders–Frykberg classification ( n = 10), 23–30,32,39 and Brodsky classification ( n = 1), 34 in detail, 22 available only for those in remission 38 or unreported ( n = 6) 21,31,33,35–37 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Frequency of CTDs monitoring varied from every week 31 to every 12 weeks ( n = 2) 33,39 (Table 2). Usually, CTD monitoring took place every one to six weeks during immobilisation in the majority (14 of 19) of studies (see Table 2) 21–27,31,32,34–38 and as frequent as every 1–3 weeks ( n = 8) 21,23–25,31,32,37,38 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations